Pain Reduction Techniques to Overcome Back Pain Complaints in Third Trimester of Pregnancy - Sri Maryati; Karwati Karwati; Damai Yanti (Health Notions, 2022)
The problem that is often experienced by pregnant women in the third trimester is low back pain, it is estimated that around 70% of women complain of some form of low back and back pain at some point in pregnancy, childbirth and post partum. One of the therapy that can be given to mothers with low back pain is acupressure. The purpose of the study was to determine the effect of pain reduction techniques with acupressure to overcome complaints of low back pain in the third trimester of pregnancy. The design of this study was one group pre-test post-test. The sample was taken by accidental sampling, with the research subjects being pregnant women in the third trimester who visited PMB "K" in March 2021 to May 2021. The statistical test used the Wilcoxon test. The results showed that the average degree of back pain before being given acupressure: median = 3.00, standard deviation = 2,917. The average degree of back pain after being given acupressure: median = 0.00, standard deviation = 2.095. There was an effect of acupressure on the pain scale of pregnant women with back pain with p-value of 0.000. It can be concluded that acupressure massage is a technique for reducing back pain experienced by pregnant women, which can occur in the first trimester of pregnancy and is increasingly being complained of in the third trimester of pregnancy. It is hoped that massage techniques can be taught by health workers, especially midwives as female companions to the patient's family, especially husbands so that they can do it independently. Keywords: pain reduction techniques; back pain complaints